Altitude training - Facts and myths - Niederseer, D.; Niebauer, J. (2013)
The question "Altitude training: what for?", "Altitude training: for whom?", "Why is there a debate?", "Doping or not? Role of artificially-induced hypoxic conditions", "Is there Evidence for changes in performance?" and others are considered. Physiological changes during/after AT are debated. Conclusion: - Current literature DOES NOT clearly support the common notion that altitude training will generally lead to improved endurance or performance. - Improvements in economy of 3-6% after various hypoxic interventions have not consistently been shown to correlate with performance! - Responders and non-responders need to be identified in order to allow adequate exercise prescription.